Investigation of Wave Processes in Ferrite-Ferroelectric Magnonic Crystal with a Slot Transmission Line - A. A. Nikitin; A. A. Nikitin; A. B. Ustinov; A. A. Semenov (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The microwave properties of the ferrite-ferroelectric magnonic crystals with a slot transmission line were investigated. Dispersion and transmission characteristics of the spin-electromagnetic waves propagating in such structures were obtained. The influence of various parameters of the microwave waveguide structure on the transmission coefficient of the ferrite-ferroelectric magnonic crystal was investigated. In particular, the electric tuning of the transmission coefficient was demonstrated in the range of 2.8 MHz for electric voltage of 200 V. The range of the magnetic tuning was 89 MHz for the external magnetic field variation from 1325 Oe to 1350 Oe.